Three-year outcomes of cranial nerve stimulation for obstructive sleep apnea: the STAR trial - Woodson, B. Tucker; Maurer, Joachim T. (Otolaryngology - head and neck surgery, 2016)
Objective: To describe the 36-month clinical and polysomnography (PSG) outcomes in an obstructive sleep apnea (OSA) cohort treated with hypoglossal cranial nerve upper airway stimulation (UAS). Study Design: A multicenter prospective cohort study. Setting: Industry-supported multicenter academic and clinical setting. Subjects: Participants (n = 116) at 36 months from a cohort of 126 implanted participants. Methods: Participants were enrolled in a prospective phase III trial evaluating the efficacy of UAS for moderated to severe OSA. Prospective outcomes included apnea-hypopnea index, oxygen desaturation index, other PSG measures, self-reported measures of sleepiness, sleep-related quality of life, and snoring. Results: Of 126 enrolled participants, 116 (92%) completed 36-month follow-up evaluation per protocol; 98 participants additionally agreed to a voluntary 36-month PSG. Self-report daily device usage was 81%. In the PSG group, 74% met the a priori definition of success with the primary outcomes of apnea-hypopnea index, reduced from the median value of 28.2 events per hour at baseline to 8.7 and 6.2 at 12 and 36 months, respectively. Similarly, self-reported outcomes improved from baseline to 12 months and were maintained at 36 months. Soft or no snoring reported by bed partner increased from 17% at baseline to 80% at 36 months. Serious device-related adverse events were rare, with 1 elective device explantation from 12 to 36 months. Conclusion: Long-term 3-year improvements in objective respiratory and subjective quality-of-life outcome measures are maintained. Adverse events are uncommon. UAS is a successful and appropriate long-term treatment for individuals with moderate to severe OSA.